12. Inventory Of Coast Birds In Coast Coast Beach Village Liang, Central Maluku Regency - Sunaryo Sunaryo; M. Moniharapon; La Eddy (Jurnal Medika Veterinaria, 2021)
A total of 437 bird species out of 1771 bird species found in Indonesia are protected birds. Birds need and choose certain places to eat, nest, lay eggs, grow up and protect itself from predators). Habitat selection by shorebirds both daily and seasonal is closely related to changes in habitat Coastal waters are wetlands as important habitats for shorebirds such as breeding grounds, nesting, raising their offspring, looking for food, drinking water sources, shelter and social interaction. The presence of shorebirds in wetlands is influenced by many factors including availability, height and water quality, food availability, shelter, nesting and predators The human presence becomes a very important factor for shorebirds, such as in the village liang beach. Liang village beach has been used as a tourist area on the island of Ambon. This beach is a habitat for shorebirds. Therefore, the presence of shorebirds is very important because it is associated with the development of a sustainable beach, especially towards ecotourism. This study aims to inventory the types of shorebirds that exist on the coast of Liang Village, Salahutu District, Central Maluku Regency, Maluku Province. This research was conducted to determine the types of shorebirds on the coast of the village burrow. The results showed that the number of bird species found at the station on the Coastal Coast of Liang Village were species of Pengalahan bird (Numenius phaeopus), Asian plover (Charadrius veredus), Great Kedidi (Calidris tenuirostris), Pantai Trinil (Actitis hypoleucos), Trinil Semak (Tringa glreola) ), Kedidi Putih (Calidris alba), Little Egret (Egretta garzetta). The number of bird species at station II is greater than station I and station III.